2007
DOI: 10.1001/archopht.125.7.895
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Therapy for the Treatment of Refractory Ocular Inflammatory Disease

Abstract: To report the outcomes of infliximab therapy in the treatment of ocular inflammatory disease refractory to traditional immunomodulatory therapy (IMT). Methods:We retrospectively reviewed the medical records of 27 patients. All patients had noninfectious ocular inflammatory disease refractory to traditional IMT and received 5 mg/kg of infliximab at 2-week to 8-week intervals. Main outcome measures were clinical response, reduction in concomitant IMT, and adverse effects. Cumulative incidences of inflammation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 21 publications
(36 reference statements)
1
77
0
10
Order By: Relevance
“…[9][10][11] The patient has to date received 5 infliximab infusions and has been tapered off prednisone. Her vision and inflammation have remained stable for 3 months off of prednisone; her pain is slowly improving (Figure 1H).…”
mentioning
confidence: 99%
“…[9][10][11] The patient has to date received 5 infliximab infusions and has been tapered off prednisone. Her vision and inflammation have remained stable for 3 months off of prednisone; her pain is slowly improving (Figure 1H).…”
mentioning
confidence: 99%
“…Data were analyzed using the statistical package for the social sciences (version 19). Chi square test of association was used to compare between proportions.…”
Section: Discussionmentioning
confidence: 99%
“…11,18 According to use of DMARD alone or DMARD and Biological Agents as a treatment for articular and extra-articular manifestations in RA patients, we found that there is no statistical significance relationship between the curable effects of them and ocular manifestations in RA patient, while studies were done by Gordana Zlatanović et al and others show that (DMARDs) are necessary to improve tear production and to resolve severe ocular complications in RA patients like Cyclosporine A, or a monoclonal antibody to TNF-alpha such as infliximab. 19,21 …”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…[29][30][31] Vogt-Kayanagi-Harada (VGH) hastal›¤›, JIA, sklerit, ankilozan spondilit, psoriazis gibi çok farkl› etyolojilere ba¤l› intraoküler inflamasyonlar›n infliksimab ile kontrol edilebildi¤i bildirilmifltir. [32][33][34][35][36][37] Ayr›ca farkl› endikasyonlarla non-enfektif intraoküler inflamasyonu bulunan olgularda ilac›n intravitreal uyguland›¤›nda makula öde-minde ve görme keskinli¤i üzerine anlaml› olumlu etkisi oldu¤u gösterilmifltir. 38 Ancak diabetik makula öde-mi veya yafla ba¤l› makula dejeneresans› olgular›nda intravitreal infliksimab enjeksiyonunun iyi tolere edilemedi¤i ve retinaya toksik etkisinin oldu¤u bildirilmifltir.…”
Section: Tnf Antagonistleriunclassified